Planetens floder: Flodmotiver i tidlig moderne fransk litteratur (1573-1632) - Damgaard Hansen, Malte (Passage - Tidsskrift for litteratur og kritik, 2024)
By examining river motifs in the works of Jean-Antoine de Baïf, Michel de Montaigne, and Samuel de Champlain, this article discusses rivers in the French Renaissance as a destabilizing figure, which questions human position within a nonhuman environment.